Exploitation of Natural Resistance Genes, Mutation and Phytosanitation to Eliminate Cassava Geminiviruses - Kung’u, Mercy Wambui (University of the Witwatersrand, Johannesburg, 2024)
Not Available
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg,
Keywords: Cassava mosaic disease; Natural Resistance Genes; Mutation; East Africa cassava mosaic virus; Phytosanitation; Hydrogen peroxide; Salicylic acid; Hot water; Resistance genes; Gene expression; Ethyl methane sulfonate; UCTD; SDG-3: Good health and well-being